(untitled) (Research, Society and Development, 2023)
Introduction: The pandemic of COVID-19 shook the foundations of modern societies, bringing numerous questions about its functioning, which should be analyzed, especially by the interrelation with chronic diseases such as Diabetes. Objective: This study aimed to evaluate the pathogenic convergence points between SARS-CoV-2 infection and Type 2 Diabetes Mellitus, as well as the effect on patient prognosis. Materials and Methods: This is an integrative literature review about the pathophysiological integration between COVID-19 and Type 2 Diabetes Mellitus. The PICO strategy was used to develop the guiding question. Moreover, the descriptors "COVID-19"; "Diabetes Mellitus"; "Physiology" were cross-referenced with the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Ebscohost, Google Scholar, and Virtual Health Library (VHL) databases. Results and Discussion: A significant portion of the articles indicated an interrelationship between the pathophysiological mechanisms of COVID-19 and Type 2 Diabetes Mellitus, especially in the exacerbation of the immune response and direct damage to pancreatic cells, which result in a worse prognosis of the viral infection. Conclusion: It was possible to notice that both diseases have pathogenic interaction points, reinforcing the need to re-signify the health-disease process, aiming to understand the proper functioning of the pathophysiological mechanisms of each one of them.